Identification of Key Genes Affecting the Tumor Microenvironment and Prognosis of Triple-Negative Breast Cancer - Yi, Jiarong; Zhong, Wenjing; Wu, Haoming; Feng, Jikun; Zouxu, Xiazi; Huang, Xinjian; Li, Siqi; Shuang, Zeyu (Frontiers in Oncology, 2021)
Abstract Tumor microenvironment (TME) plays an important role in the development of many cancers. However, the roles of TME in breast cancer, especially triple-negative breast cancer (TNBC), are not well studied. This study aimed to identify genes related to tumor microenvironment and prognosis of TNBC. To identify differentially expressed genes (DEG) in the TME of TNBC, combined data from the Cancer Genome Atlas (TCGA) and Estimation of Stromal and Immune cells in Malignant Tumor tissues using Expression data (ESTIMATE) datasets was used. Then, survival analysis was performed to analyze the relationship between TME and prognosis of TNBC, as well as determine genes differentially expressed. Genes showing significant differences were scored as alternative genes. A protein-protein interaction (PPI) network was constructed and functional enrichment analysis was conducted using the DEG. Genes with a degree beyond 5 in the PPI network were regarded as hub genes, while genes with a degree beyond 10 in the PPI network were regarded as key genes. Finally, CCR2 and CCR5 were identified as key genes in TME and prognosis of TNBC. These results were verified using Gene Expression Omnibus (GEO) datasets and immunohistochemistry of TNBC patients. In conclusion, CCR2 and CCR5 are key genes in TME and prognosis of TNBC with the potential of prognostic biomarkers in TNBC.